Spacer acquisition by Type III CRISPR–Cas system during bacteriophage infection of Thermus thermophilus - Artamonova, Daria (Nucleic Acids Res, 2020)
Type III CRISPR–Cas systems provide immunity to foreign DNA by targeting its transcripts. Target recognition activates RNases and DNases that may either destroy foreign DNA directly or elicit collateral damage inducing death of infected cells. While some Type III systems encode a reverse transcriptase to acquire spacers from foreign transcripts, most contain conventional spacer acquisition machinery found in DNA-targeting systems. We studied Type III spacer acquisition in phage-infected Thermus thermophilus, a bacterium that lacks either a standalone reverse transcriptase or its fusion to spacer integrase Cas1. Cells with spacers targeting a subset of phage transcripts survived the infection, indicating that Type III immunity does not operate through altruistic suicide. In the absence of selection spacers were acquired from both strands of phage DNA, indicating that no mechanism ensuring acquisition of RNA-targeting spacers exists. Spacers that protect the host from the phage demonstrate a very strong strand bias due to positive selection during infection. Phages that escaped Type III interference accumulated deletions of integral number of codons in an essential gene and much longer deletions in a non-essential gene. This and the fact that Type III immunity can be provided by plasmid-borne mini-arrays open ways for genomic manipulation of Thermus phages.